2022
DOI: 10.2147/jpr.s366536
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pain and Its Risk Factors Among ICU Personnel in Tertiary Hospital in China: A Cross-Sectional Study

Abstract: Background: Although pain is commonly observed among medical staff, studies on pain among intensive care unit personnel are uncommon, especially intensive care unit (ICU) doctors and workers. Moreover, few studies have focused on the prevalence of pain and the associated factors. Purpose:The aim of this study was to estimate the prevalence of pain among ICU personnel (including doctors, nurses and workers) and explore the risk factors for their pain. Methods: We conducted an online survey that included sociode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Musculoskeletal pain is a common symptom among healthcare workers, including physicians. Several studies have reported a high prevalence of musculoskeletal pain among physicians across different specialties [1][2][3][4][5]. Various workplace risk factors have been implicated in the occurrence of musculoskeletal pain among healthcare workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Musculoskeletal pain is a common symptom among healthcare workers, including physicians. Several studies have reported a high prevalence of musculoskeletal pain among physicians across different specialties [1][2][3][4][5]. Various workplace risk factors have been implicated in the occurrence of musculoskeletal pain among healthcare workers.…”
Section: Introductionmentioning
confidence: 99%
“…Various workplace risk factors have been implicated in the occurrence of musculoskeletal pain among healthcare workers. These include ergonomic factors and physical job demands [6,7], long working hours and night shifts [8], psychosocial and emotional burdens of the profession [3] and perceptions about workplace support [7]. A recent study conducted in Egypt found the prevalence of musculoskeletal disorders among physicians to be as high as 74% [9].…”
Section: Introductionmentioning
confidence: 99%